Prinsip, Implementasi, dan Tantangan Kontemporer Dalam Hukum Bisnis Syariah - Anggun Feby Ivana Putri; Anisa Siti Nurjanah; Febrina Friska; Sri Handayani (Jurnal Riset Multidisiplin Edukasi, 2025)
Law in Sharia Business is the main pillar of the Islamic economic system that aims to create transparency, justice, and blessings in economic activities. The purpose of this study is to explain the basic principles in Sharia business law, the implementation of business practices, and challenges in the modern context. This study uses a qualitative method with academic journals and related book literature research approaches. The results of the study indicate that official Sharia law can create an ethical and sustainable economic system, but its implementation poses challenges, including lack of public literacy, limited regulations and adaptation to technological developments. Cooperation between scientists, academics and supervisory authorities is needed to strengthen the implementation of Sharia business and to answer the challenges of globalization. To overcome these challenges, synergy is needed between scientists, academics, business people, and supervisory authorities to strengthen a Sharia business law system that is responsive to the dynamics of the times. With joint efforts, it is hoped that this system will be able to answer the needs of contemporary economies without abandoning Sharia principles.